Komposisi Hasil Tangkapan Ikan dan Tingkat Keramahan Lingkungan Alat Tangkap Sero di Desa Tapulaga, Sulawesi Tenggara - Rita Bubun; Fajriah Fajriah; Nelly Marlisa (Jurnal Airaha, 2015)
The principle development fishing in substance lead to the use of resources to optimal and rational for fishermen society welfare, without causing damage resources, environmental and sustaineble fisheries. The cath that fesiable to get on operation "sero" and analyzed levels of sustainable on a get "sero" in the Tapulaga Soropia Subdistrict Southeast Sulawesi. Research method is using the method survey. analysis data is descriptive kuantitatif to determine a measure of lenght fish and the level sustainable of "sero". the research result show that (1) tehe composition of the catch based on type consisting of 17 spesies. Domination species is Loligo spp in 24%. The composition of lenght fish in 52%, dominated by lenght fish of 10 - 19 cm; (2) the level of sustainable by "sero" is the value of 25. Basedon the values then "sero" be categorized as a sustainable fishing gear.